Hypertension in the Elderly: Prevalence, awareness and health seeking behaviour (Journal of Dhaka National Medical College & Hospital, 2014)
Background : Hypertension is the commonest cardiovascular disorder, among elderly population. It is evident that the urban poor living in slums has poor access to healthcare, partly related to their poor purchasing ability.Objectives : Present study was undertaken to determine treatment seeking behaviour and health expenditure incurred among elderly hypertensive.Material and methods : A cross sectional descriptive study was conducted among elderly population aged 51 years and above in Urban slums of Moghbazar attached to Dhaka Community Medical College and Hospital from October to December 2013.Results : Out of 1041 respondents, majority 604 (58.0%) were from the age group of 61 – 70 years. Their mean age was 61.77 years; (SD±6.038). Majority of the geriatrics respondents 624 (59.9%) were male and 417 (40.1%) were female. Most of the respondents 820 (78.8%) were illiterate, 144 (13.8%) were unemployed and 616 (59.2%) were from nuclear family. Their average monthly family income were 72.02.43, SD = ±2969.90 Taka. Of the 660 hypertensive’s, 120 (18.2%) were newly diagnosed during he study and 540 (81.8%) were known hypertensive’s. Of the 540 (81.8%) hypertensive patients only 180 (33.3%) took regular treatment, and 360 (66.7%) did not seek treatment regularly. Majority of patients (77.7%) visited hospital for obtaining treatment for hypertension. Regarding the opinion for expenditure, 458 (44%) gave their opinion for transportation cost as average, 487 (46.8%) and 498 (47.8%) respondents mentioned doctor’s fee and medicine cost were high.Conclusion : Appropriate strategies are important to diagnose early, initiate, aggressive treatment and making awareness of hypertension to reduce the prevalence and to lead a healthy life of elderly population in Urban slums.J. Dhaka National Med. Coll. Hos. 2014; 20 (02): 46-50